FATWA ULAMA DAN EKSISTENSINYA DALAM MENYELESAIKAN PROBLEMA UMAT ISLAM DI INDONESIA (Studi terhadap Fatwa MUI dalam Pelaksanaan Ibadah Akibat Kasus Corona) - Muh. Haras Rasyid (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2021)
As stated in the title of this paper, the problem is how the existence and contribution of ulama's fatwas, both individually and in groups, in solving problems that exist among Muslims. The existence of ulama's fatwa is very strategic and cannot be denied that it has made a real contribution to the life of the nation and state in Indonesia. As far as this research is carried out, the fatwa of ulama, especially those born from the Indonesian Ulama Council (MUI), is an Islamic legal decision taken by the ulama which of course aims to solve actual problems for Muslims. One of the principles is when the issuance of several MUI fatwas as a real contribution in responding to the prevention of the spread of the Covid 19 virus. -in the middle of the covid 19 outbreak, justified by the Shari'ah